Experimental and Numerical Investigation of Strain Rate Dependent Flow and Fracture Behavior of 6181A-T4 Alloy Using the Johnson–Cook Model - Ecenur Öztürk; Onur Cavusoglu; Ahmet Güral (Crystals, 2025)
The use of aluminum alloys for lightweighting in the automotive industry is becoming widespread. In this study, Johnson–Cook plasticity and damage model parameters were determined to predict the plasticity and damage behavior of 6181A-T4 sheet material using finite element analysis software. Uniaxial tensile tests were performed at four different deformation rates (0.0083–0.333 s−1) using tensile test specimens with four different triaxiality values (0.33, 0.36, 0.45, and 0.74). For a 3 mm thick 6181A-T4 aluminum alloy sheet, Johnson–Cook plasticity parameters were determined by the curve fitting method, and damage parameters were optimized using LS-OPT 7.0 software. Finite element analyses using Johnson–Cook plasticity and damage model parameters were compared with the experimental results, and it was observed that the finite element analyses produced very successful predictions. With the increase in strain rate, the yield strength increased, while the tensile strength showed limited change; uniform elongation, coefficient of hardening, and toughness showed a decreasing trend, and the fracture mode showed a transition from ductile to more brittle behavior. The coefficient of determination (R2) values between the Johnson–Cook model and the experimental data ranged from 0.8601 to 0.9837 depending on the strain-rate value.